Internet Addiction Neuroscientific Approaches and Therapeutical Interventions - Montag, Christian; Reuter, Martin (Studies in Neuroscience, Psychology and Behavioral Economics,, 2015)
This book combines a scholarly introduction with state-of-the-art research in the characterization of Internet addiction. It is intended for a broad audience including scientists, students and practitioners. The first part of the book contains an introduction to Internet addiction and their pathogenesis. The second part of the book is dedicated to an in-depth review of neuroscientific findings which cover studies using a variety of biological techniques including brain imaging and molecular genetics. The last part of the book will focus on therapeutic interventions for Internet addiction.